Getting into commercial production (bis) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2007)
A church-linked development agency in Zimbabwe is supporting farmers to grow and market various medicinal herbs.